Impact of Video Education on Mothers’ Knowledge of Early Initiation of Breastfeeding in Makassar - Ummul Fadhilah; Fitria Fitria; Sri Muliani (Jurnal EduHealth, 2025)
Early Initiation of Breastfeeding (IMD) is a critical intervention for improving maternal and neonatal health outcomes. However, maternal knowledge regarding IMD remains inconsistent, particularly in urban settings. This study aimed to examine the effect of video-based education on pregnant women’s knowledge of IMD in Makassar City.  This study employed a quasi experimental one-group pretest–posttest design, involving 35 third-trimester pregnant women selected through purposive sampling. Data were collected using a 20-item IMD knowledge questionnaire. The intervention consisted of an educational video on IMD, with knowledge assessed before and after viewing. The results indicated a significant improvement in maternal knowledge, with mean scores increasing from 11.14 to 16.57. A paired t-test revealed t = 14.82 and p = 0.000 (p < 0.05), confirming that video-based education has a significant effect on enhancing knowledge. The study concludes that educational videos are an effective, engaging, and accessible medium for strengthening maternal understanding of IMD and may serve as an evidence-based strategy for antenatal education in healthcare facilities.